Role of Integrins in Sperm Activation and Fertilization - Merc, Veronika; Frolikova, Michaela; Komrskova, Katerina (International journal of molecular sciences, 2021)
In mammals, integrins are heterodimeric transmembrane glycoproteins that represent a large group of cell adhesion receptors involved in cell-cell, cell-extracellular matrix, and cell-pathogen interactions. Integrin receptors are an important part of signalization pathways and have an ability to transmit signals into and out of cells and participate in cell activation. In addition to somatic cells, integrins have also been detected on germ cells and are known to play a crucial role in complex gamete-specific physiological events, resulting in sperm-oocyte fusion. The main aim of this review is to summarize the current knowledge on integrins in reproduction and deliver novel perspectives and graphical interpretations presenting integrin subunits localization and their dynamic relocation during sperm maturation in comparison to the oocyte. A significant part of this review is devoted to discussing the existing view of the role of integrins during sperm migration through the female reproductive tract; oviductal reservoir formation; sperm maturation processes ensuing capacitation and the acrosome reaction, and their direct and indirect involvement in gamete membrane adhesion and fusion leading to fertilization.
Keywords: sperm activation; interakce spermie a vajíčka; Male; oocyty; Sperm Capacitation; Integrins; fusion; integriny; integrins; Spermatozoa; mužské pohlaví; Sperm-Ovum Interactions; oocyte; sperm; reproduction; Animals; lidé; kapacitace spermií; ženské pohlaví; Humans; zvířata; spermie; Female; Oocytes